STUDI EKSPERIMEN PENGARUH PENGGUNAAN BAHAN BAKAR MINYAK JENIS PREMIUM, PERTALITE, DAN PERTAMAX TERHADAP KINERJA KONSUMSI BAHAN BAKAR MOBIL LCGC 1200 CC - Hans Ludwig Jonathan (2021)
The purpose of this experimental study is to find out the performance of the Low -Cost Green Car (LCGC) car engine by using various fuel type, such as Premium 88, Pertalite 90, and Pertamax92. LCGC cars from various brands and types have been sold to the public and have received very positive responses. The performance of an engine depends on various factors, such as the variation of fuel used. Each fuel will be tested on an LCGC car using a gas analyzer and dynostest connected to a computer. The graph variations of torque and power will be processed on the computer starting from the engine idle to 6500 rpm. After the experimental study, the engine can achieve the highest power and torque when using Pertamax 92 fuel, followed by Pertalite90 in second place and Premium88 in third place with the lowest power figures. Pertamax92 fuel reaches a maximum torque of 115.4 nm at 5000 rpm and reaches a maximum power of 98 hp at 6500 rpm. Overall, the exhaust gas emissions of HC, CO, CO2, and O2 from Pertamax92 fuel are less than the other two fuels, so it can be concluded that Pertamax 92 is better for the environment when compared to Pertalite 90 and Premium 88 fuels. In-order to obtain more in-depth analysis results, other studies are still needed, such as do some trials on uneven roads, uphill, and using fuel with higher octane number.